Cryptocurrency Investing: Millennial Decision Making - Kiruba, Angelin S, DR; R, Bharathi, DR; N, Madhumithaa, DR (UI Scholars Hub, 2023)
Investor perceptions of various investment modes can differ based on factors such as experience, earnings, risk tolerance, liquidity preferences, and so on. Understanding the viewpoints of young in- vestors is essential when assessing cryptocurrency investments. This study evaluates the investment decisions of 103 young investors in the cryptocurrency market, using regression and factor analysis for data analysis. The findings indicate that investors have a fundamental understanding of the risks associated with cryptocurrency investments. However, there is a notable need for enhancing the ef- fective management of these risks. The study affirms the reliability of the measures used, accurately capturing the underlying factors pertinent to cryptocurrency investment.